2011
DOI: 10.4314/sajas.v41i1.66032
|View full text |Cite
|
Sign up to set email alerts
|

Live animal and carcass characteristics of South African indigenous goats

Abstract: Eighty-nine intact male, castrates and female South African indigenous goats in three age groups (0, 2 -6 and 8 permanent incisors) and two pre-slaughter conditioning groups; namely, the non-conditioned which were slaughtered within three months of purchase and the pre-slaughter conditioned, which were slaughtered 6 -10 months after purchase or birth were used. The effect of sex, age and pre-slaughter conditioning on live animal, carcass dimensions and carcass composition were evaluated. The goats were large w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 20 publications
7
38
1
Order By: Relevance
“…It should be noted that tissue distribution in both genotypes studied averaged at 70% lean, 17% bone and 13% fat. These values are within ranges reported for South African indigenous goats and other goat breeds (Devendra & Owen, 1983, Simela et al, 2011. These results show that the indigenous Mubende goat has a high meat production potential and compares with its Boer crossbreds, one of the world's goat meat producing breeds.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It should be noted that tissue distribution in both genotypes studied averaged at 70% lean, 17% bone and 13% fat. These values are within ranges reported for South African indigenous goats and other goat breeds (Devendra & Owen, 1983, Simela et al, 2011. These results show that the indigenous Mubende goat has a high meat production potential and compares with its Boer crossbreds, one of the world's goat meat producing breeds.…”
Section: Resultssupporting
confidence: 85%
“…Traits such as lean: bone ratio, confirmation, morphological measurements and the distribution of fat within the carcass are of great importance in meat production (Chacón et al, 2011;Simela et al, 2011). In Uganda, goat meat production relies on local, indigenous herds raised under traditional production systems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kadim et al (2006), in their study with three Omani goat breeds, reported that the Jabal Akhdar goat breed had higher carcass weight and hence higher chilling loss (shrinkage) compared with the Dhofari and Jabal Akhdar breeds. Overall, the chilling loss for this study was marginally higher than 3%, which is usually estimated for goat carcasses (Webb et al, 2005, Simela et al, 2011.…”
Section: Resultsmentioning
confidence: 53%
“…The proportion of high value cuts is also an important indication of the overall value of the carcass. Carcasses attributes are principally concerned with the quantity of saleable meat that can be obtained, but also have significant implications on the technological properties of the meat, such as pH, colour and tenderness (Simela et al, 2011).Some studies have indicated that carcass quality can differ significantly among breeds, particularly among light lambs, but to some extent differences depend on the criteria used in comparisons (same weight, same age, or same proportion of mature weight). However, breed is much less important in lamb meat quality than other factors (Santos Sylva et al, 2002;Martínez-Cerezo et al, 2005;Pérez et al, 2007;Miguélez et al, 2006).…”
mentioning
confidence: 99%